The impacts of inhalation aromatherapy with lavender essential oil on students' test anxiety: a randomized placebo-controlled clinical trial - Esmat Jafarbegloo; Hoda Ahmari Tehran; Sareh Bakouei (Institue of Medicinal Plants, ACECR, 2020)
Background: Test anxiety (TA) can hinder students' academic achievement and cause them educational decline and psychological problems. Objective: The effect of inhalation aromatherapy with lavender essential oil on nursing students' test anxiety was investigated. Methods: This was a quasi-experimental study was conducted on 33 nursing students who had taken the Community Health Nursing II course and were going to take its final exam. Before taking the exam of the course, the students were allocated to the aromatherapy (n = 16) and the control groups (n = 17). For the aromatherapy group, ten drops of lavender essential oil was added to one liter of water and the solution was distributed in the room space for fifteen minutes by using a humidifier. However, the humidifier which was used for the control group included of only pure water without any essential oil. The students' test anxiety was measured both before and after the study intervention by employing the Test Anxiety Inventory. Results: There was no significant difference between the study groups regarding the participating students' demographic characteristics as well as the pretest and the posttest values of test anxiety. However, within-group comparisons indicated that in the aromatherapy group, the posttest value of test anxiety was significantly lower than the pretest value. Conclusions: The findings indicated that inhalation aromatherapy with lavender essential oil had no positive effects on students' test anxiety. However, as the level of test anxiety in the aromatherapy group decreased significantly after the intervention and the students in this group reported that aromatherapy was pleasant to them. Aromatherapy is probably insignificant in alleviating acute or state anxieties.